Metode Dempster Shafer pada Sistem Pakar Penentuan Penyakit Bayi - Herman Herman; Sunardi Sunardi; Virasanty Muslimah (JURIKOM (Jurnal Riset Komputer), 2022)
The baby’s immune system is still weak so it needs special attention. Parents are advised to check their baby to the health service regularly. There are along queues due to limited hours of service or doctor’s practice in serving patients. Parents need expert systems to facilitate detection and early prevention. Systems that try to adapt human knowledge to computers to solve problems in the way that experts do are called expert systems. The dempster shafer method will be used in this study as an expert system for infant disease. The way the dempster shafer works is by defining each sysptom with a density value. This study uses 23 type pf symptoms with 3 types of disease. Dengue fever can be identified based on 11 symptoms, 13 sysmptoms of malaria, and 14 symptoms of diarrhea. The results of  calculation on a case study found that the Malaria (TOD02) was the strongest with a value of 0,83 or 83% obtained from the symptoms of the body shivering but sweating (SOD02), vomiting (SOD03), blood in the stool (SOD06), fever appears and disappears simultaneously (SOD16), and red eyes (SOD17) so it is believed that the baby’s disease is Malaria